2017
DOI: 10.1177/1010428317694575
|View full text |Cite
|
Sign up to set email alerts
|

Roles of zinc-fingers and homeoboxes 1 during the proliferation, migration, and invasion of glioblastoma cells

Abstract: Zinc-fingers and homeoboxes 1 (ZHX1) is a nuclear transcription repressor and known to be involved in cell differentiation and tumorigenesis. However, the pathophysiological roles of ZHX1 have not been characterized in glioblastoma. We examined ZHX1 expression in glioblastoma patients' tissues and analyzed overall survival of the patients based on expression level of ZHX1. We also examined the effects of ZHX1 on proliferation and motility of glioblastoma cells. In silico analysis and immunohistochemical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…However, two recent studies suggested that ZHX1 may serve as an oncogene in glioblastoma and cholangiocarci- noma 34,35. Upregulated ZHX1 expression in tumor specimens compared with that in normal tissues has been found to be correlated with reduced survival of cancer patients 34,35. The observations in glioblastoma and cholangiocarcinoma are consistent with our findings, ie, patients with high ZHX1 expression showed significantly prolonged OS than those with low ZHX1 expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, two recent studies suggested that ZHX1 may serve as an oncogene in glioblastoma and cholangiocarci- noma 34,35. Upregulated ZHX1 expression in tumor specimens compared with that in normal tissues has been found to be correlated with reduced survival of cancer patients 34,35. The observations in glioblastoma and cholangiocarcinoma are consistent with our findings, ie, patients with high ZHX1 expression showed significantly prolonged OS than those with low ZHX1 expression.…”
Section: Discussionsupporting
confidence: 92%
“…ZHX1, the first identified factor of this family, has been proposed as a tumor suppressor in many cancer types 29–33. However, two recent studies suggested that ZHX1 may serve as an oncogene in glioblastoma and cholangiocarci- noma 34,35. Upregulated ZHX1 expression in tumor specimens compared with that in normal tissues has been found to be correlated with reduced survival of cancer patients 34,35.…”
Section: Discussionmentioning
confidence: 99%
“…is also shown to be an oncogene, and its high expression can facilitate TWIST1 and SNAI2 expression, comprising crucial modulators in epithelial-mesenchymal transition. 22 It is worth noting that elevated ZHX1 expression is correlated with a poor prognosis in GBM patients, and an in vitro study suggested that ZHX1 inhibits GBM cell apoptosis via Bax down-regulation and Bcl-2 up-regulation. 43 In the present study, we showed that miR-23b-3p could negatively modulate ZHX1 expression; in addition, SNHG17 knockdown could reduce ZHX1 expression, thus clarifying the downstream mechanism of SNHG17/ miR-23b-3p and explaining the dysregulation of ZHX1 in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cholangiocarcinoma, hepatocellular carcinoma and cervical cancer, ZHX1 promotes cancer progression 40–42 . In glioma, ZHX1 is also shown to be an oncogene, and its high expression can facilitate TWIST1 and SNAI2 expression, comprising crucial modulators in epithelial–mesenchymal transition 22 . It is worth noting that elevated ZHX1 expression is correlated with a poor prognosis in GBM patients, and an in vitro study suggested that ZHX1 inhibits GBM cell apoptosis via Bax down‐regulation and Bcl‐2 up‐regulation 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation